CASE REPORT: ANAPHYLAXIS DURING AZITHROMYCIN PROVOCATION - Ayşe Süleyman; Esra Özek Yücel; Sevgi Sipahi Çimen; Zeynep Hızlı Demirkale; Cevdet Özdemir; Zeynep Altınel; Nermin Güler (İstanbul Tıp Fakültesi Dergisi)
Clarithromycin and azithromycin are the most frequently prescribed oral macrolide antibiotics for children. Macrolides are relatively safe antibiotics due to their low allergenicity, but are nevertheless known to cause hypersensitivity reactions. Azithromycin appears to be responsible for severe reactions more often than clarithromycin. The most common reactions are maculopapular exanthems, and macrolide-induced anaphylaxis is exceptionally rare. Skin tests are not enough for the diagnosis of macrolide allergies, and oral provocation tests are necessary for a definite diagnosis. Here, we present a case of anaphylaxis during oral provocation with azithromycin, in which intolerance to amoxicillin-clavulanic acid and clarithromycin have been verified by provocation testing previously.